A convenção nº 158 da Organização Internacional do Trabalho e a legislação brasileira - Husek, Renata (2010)
Convention No. 158 of the International Labor Organization, in force within the international sphere since November 23, 1985, prohibits arbitrary dismissal of employees. Although Brazil ratified the Convention on January 5, 1995 and it came into force within Brazil as from publication of Promulgation Decree 1855 of 1996, the effects of said Convention were vacated by the Brazilian President on December 20, 1996. Within the international sphere, this vacation has been considered valid, but the lawfulness of such vacation is still under discussion on domestic terms, as per Direct Action for Unconstitutionality No. 1625. We conclude that a vacating act performed solely by the Brazilian President is valid and, therefore, International Labor Organization Convention No. 158 is currently not in force in Brazil. On the other hand, we believe there is no legal obstacle for Brazil to ratify, once again, International Labor Organization Convention No. 158, which seems to us to the course of action to be taken in view of the need of regulating article 7, item I of the Brazilian Federal Constitution, as well as due to the latest court decisions warning about the absence of legal guidelines for formal recognition of collective termination of employment contracts. If Convention No. 158 is once again ratified, its rules would be incorporated into the Brazilian legal system, being at least comparable to a constitutional rule; within this context, major changes would refer to the need of justification for termination of employment agreements, which should be based on article 482 of the Consolidated labor Law or on the employee s level of performance or on the employer s operations, as well as to incorporation of rules on collective dismissal of employees, which currently do not exist in the Brazilian legislation